A method for electrochemically synthesizing syringaldehyde compounds by using a phenyl-containing acrylic acid derivative as a substrate
Patent Information
- Application Number
- CN202611103754.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-23
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2046-07-23
AI Technical Summary
然而,在该电解液体系下,工作电流只能达到5.0mA-15.0mA,反应效率较低
(1)通过优化电极结构与电解体系,将反应电流密度提升到了100mA·cm⁻2,大幅提升了反应效率;
Smart Images

Figure CN122610104B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a method for synthesizing syringaldehyde compounds, specifically a method for electrochemically synthesizing syringaldehyde compounds using acrylic acid derivatives as substrates, belonging to the field of organic electrosynthesis technology. Background Technology
[0002] Syringaldehyde, an important class of aromatic aldehydes, is a key synthetic structural unit for constructing lignans, flavonoids, polyphenols, and their derivatives, and has wide applications in the synthesis of bioactive aromatic heterocycles and polymer precursors. Syringaldehyde also demonstrates significant value in the pharmaceutical and functional chemical fields. The methoxy and aldehyde groups in its molecular structure endow it with multiple biological activities, including antioxidant, anti-inflammatory, and antibacterial properties, exerting its effects through mechanisms such as scavenging free radicals, regulating inflammatory signaling pathways, and interfering with the integrity of microbial cell membranes. Furthermore, thanks to its origin from natural plants such as cloves and wood, and its mild aroma, syringaldehyde is often used as a high-value fragrance ingredient in the daily chemical and food flavoring industries.
[0003] Currently, the main methods for obtaining syringaldehyde rely on extraction from natural plants or chemical oxidation synthesis of precursors such as eugenol and vanillin. However, these methods generally suffer from low extraction rates, lengthy synthesis steps, and heavy environmental burdens due to the use of heavy metal oxidants, hindering its large-scale green production. Although syringaldehyde shows significant potential in multiple fields, its efficient and atom-economical synthetic strategies, particularly the selective C–H functionalization of aromatic rings to directly introduce aldehyde groups, still face challenges in reaction selectivity and catalytic system design.
[0004] In recent years, electrochemical synthesis has provided a new approach for the sustainable preparation of syringaldehyde. Electrochemical methods replace traditional chemical oxidants with anodic oxidation, achieving a green conversion of electrons as a clean reagent. Chinese invention patent CN113073347A discloses a method for the electrochemical synthesis of syringaldehyde. This method uses 2,6-dimethoxy-4-methylphenol as a substrate, an alkaline methanol aqueous solution as the electrolyte, a titanium mesh with a thin layer of platinum nanoparticles electrodeposited on its surface as the anode and cathode, water as the oxygen source, and electrons as the clean oxidant. An oxygenation reaction occurs at the anode to generate syringaldehyde. However, under this electrolyte system, the operating current can only reach 5.0 mA-15.0 mA, resulting in low reaction efficiency. Furthermore, due to the oxygenation reaction at the anode, the strong oxidizing environment corrodes the anode, affecting its long-term cycling stability. Summary of the Invention
[0005] To address the shortcomings of existing technologies, the present invention aims to provide a method for the electrochemical synthesis of syringaldehyde compounds with high reaction efficiency and good long-term cycling stability of the electrodes.
[0006] To achieve the above objectives, the present invention adopts the following technical solution: A method for the electrochemical synthesis of syringaldehyde compounds using phenyl-containing acrylic acid derivatives as substrates includes the following steps: (1) The active metal components Pb, In, Sn, Fe, Ga, Al or Cu are decorated on the surface or interface of platinum group metals Pd, Pt, Ru or Ir in the form of oxides or atomic dispersion to precisely construct a heterojunction structure and obtain a catalyst; (2) The catalyst is modified onto carbon paper to form an electrode sheet; (3) Prepare a water-ethanol-[EMIm]BF4 electrolyte system; (4) Add the electrolyte to the diaphragmless electrolytic cell, use the electrode plates as the anode and cathode of the electrolytic cell, add a phenyl-containing acrylic acid derivative to the electrolyte, set the potential of the electrolytic cell to -0.9V and the current density to 100mA·cm -2 The reaction substrate was reduced at 30℃ using a constant current method. After the reaction was complete, the product was separated, purified, and dried.
[0007] Preferably, in step (1), the method for constructing the heterojunction structure is as follows: (i) Take 1.0 g of platinum group metal precursor and add it to oleylamine, then add 0.56 g of vitamin C and 0.72 g of CTAB, and react at 180 °C for 5 h to obtain precursor nanoparticles; (ii) The precursor nanoparticles were separated, purified, and dried, and then added to ethanol containing 4g of nano-sized conductive carbon black and ultrasonically mixed. They were then separated and dried again to obtain product A. (iii) Add all of product A by mass to the active component metal salt, stir evenly, let stand at room temperature for 0.5 h, then dry at 60 °C, and finally calcine at 200 °C for 2 h.
[0008] More preferably, in step (i), the platinum group noble metal precursor is Pd(acac)2, Pt(acac)2, Ru(acac)3 or Ir(acac)3; and the active component metal salt is Pb(acac)2, InCl3, SnCl2, Fe(acac)3, Ga(acac)3, AlCl3 or Cu(acac)2.
[0009] Preferably, in step (2), the method for modifying the catalyst onto the carbon paper is as follows: (i) Mix ethanol, Nafion solution and catalyst powder evenly, and sonicate to obtain a catalyst slurry; (ii) Apply the catalytic slurry onto carbon paper and let it dry.
[0010] Preferably, in step (3), the method for preparing the water-ethanol-[EMIm]BF4 electrolyte system is as follows: Water and ethanol were mixed at a volume ratio of 3:1, and then [EMIm]BF4 was added to make the concentration of [EMIm]BF4 0.2 mg / mL.
[0011] Preferably, in step (4), the phenyl-containing acrylic acid derivative is 3-(4-hydroxy-3,5-dimethoxyphenyl)acrylic acid, 3-(4-hydroxy-3-methoxyphenyl)acrylic acid, or 3-(4-hydroxyphenyl)acrylic acid.
[0012] Preferably, in step (4), the method for separating, purifying, and drying the product is as follows: (i) Rotary evaporation of the reaction solution yields the mother liquor; (ii) Wash the mother liquor with petroleum ether; (iii) Purify the mother liquor after washing with petroleum ether using ethyl acetate; (iv) The purified mother liquor was dried at 60°C.
[0013] The advantages of this invention are: (1) By optimizing the electrode structure and electrolysis system, the reaction current density was increased to 100 mA·cm⁻ 2 This significantly improved reaction efficiency; (2) By selecting a suitable reaction substrate (acrylic acid derivative), the synthesis reaction is carried out at the cathode (the acid undergoes a reduction reaction to produce aldehyde), which effectively alleviates the corrosion of the electrode by the strong oxidizing environment and significantly enhances the long-term cycling stability of the electrode. (3) Experiments show that the electrolysis system constructed in this invention can operate continuously and stably for more than 350 hours, and the catalytic activity has not decreased significantly, which can better meet the requirements of industrial production. Attached Figure Description
[0014] Figure 1 The images show the XRD patterns of the catalyst Pd-1 prepared by this invention and its standard card, wherein the left image is the XRD pattern of the catalyst Pd-1 prepared by this invention, and the right image is the XRD pattern of the standard card. Figure 2 These are the XRD patterns of the catalyst Pd-2 prepared by this invention and its standard card, wherein the left figure is the XRD pattern of the catalyst Pd-2 prepared by this invention, and the right figure is the XRD pattern of the standard card; Figure 3 These are the XRD patterns of the catalyst Pd-3 prepared by this invention and its standard card, wherein the left figure is the XRD pattern of the catalyst Pd-3 prepared by this invention, and the right figure is the XRD pattern of the standard card; Figure 4 It is the product prepared in Example 1. 1 Image of H-NMR detection results; Figure 5 It is the product prepared in Example 1. 13 C-NMR detection results; Figure 6 This is an MS detection result image of the product prepared in Example 1; Figure 7 This is an HPLC detection result diagram of the product prepared in Group 1 of Example 3; Figure 8 It is the product prepared in Group 1 of Example 3. 1 Image of H-NMR detection results; Figure 9 It is the product prepared in Group 1 of Example 3. 13 C-NMR detection results; Figure 10 This is the HPLC detection result of the product prepared in Group 2 of Example 3; Figure 11 It is the product prepared in group 2 of Example 3. 1 Image of H-NMR detection results; Figure 12 It is the product prepared in group 2 of Example 3. 13 C-NMR detection results; Figure 13 This is a graph showing the cycle stability test results of the electrode sheet modified with catalyst Pd-1 prepared in this invention. Detailed Implementation
[0015] The present invention will now be described in detail with reference to the accompanying drawings and specific embodiments.
[0016] I. Electrode Preparation Weigh 1.0 g of platinum group metal precursors palladium diacetylacetonate (Pd(acac)2), platinum diacetylacetonate (Pt(acac)2), ruthenium triacetylacetonate (Ru(acac)3), or iridium triacetylacetonate (Ir(acac)3) and add them to 50 mL of oleylamine. Then add 0.56 g of reducing agent vitamin C and 0.72 g of surfactant cetyltrimethylammonium bromide (CTAB), and heat to 180 °C for 5 h to obtain precursor nanoparticles. After the reaction is complete, the reaction solution is centrifuged (8000 rpm, 5 min, retaining the precipitate), washed (washing agent is a mixture of cyclohexane and ethanol in a volume ratio of 5:1), and dried (60 °C). The product is then added to ethanol containing 4 g of nano-sized conductive carbon black, ultrasonically mixed, centrifuged again (8000 rpm, 5 min, retaining the precipitate), and dried (60 °C) to obtain product A.
[0017] Product A was added to a solution of the active component metal salts platinum diacetylacetonate (Pb(acac)2), indium trichloride (InCl3), stannous chloride (SnCl2), iron triacetylacetonate (Fe(acac)3), gallium triacetylacetonate (Ga(acac)3), aluminum chloride (AlCl3), or copper acetylacetonate (Cu(acac)2). After stirring evenly, the solution was allowed to stand at room temperature for 0.5 h. The active component metal salts were then loaded onto nanoscale conductive carbon black through adsorption. Product A was mixed with the active component metal salts by an equal mass. After adsorption, the reaction solution was dried at 60℃ and then calcined at 200℃ for 2 hours. This allowed the active metal components, such as Pb, In, Sn, Fe, Ga, Al, and Cu, to be decorated on the surfaces or interfaces of platinum group metals, such as Pd, Pt, Ru, and Ir, in the form of oxides or atomic dispersions, thus precisely constructing a heterojunction structure and obtaining catalysts, which were designated as Pd-1, Pd-2, Pd-3, Pd-4, Pd-5, Pd-6, Pd-7, Pt-1, Pt-2, Pt-3, Pt-4, Pt-5, Pt-6, Pt-7, Ru-1, Ru-2, Ru-3, Ru-4, Ru-5, Ru-6, Ru-7, Ir-1, Ir-2, Ir-3, Ir-4, Ir-5, Ir-6, and Ir-7.
[0018] The specific metal components of each catalyst are shown in Table 1.
[0019] Table 1. Metal composition of each catalyst
[0020] X-ray diffraction analysis was performed on catalysts Pd-1, Pd-2, and Pd-3, respectively. The obtained XRD patterns are shown below. Figure 1 , Figure 2 and Figure 3 .
[0021] Depend on Figure 1 , Figure 2 and Figure 3 It can be seen that the XRD patterns of catalysts Pd-1, Pd-2, and Pd-3 prepared by this invention can all correspond well with their respective standard cards, proving that catalysts Pd-1, Pd-2, and Pd-3 were all successfully prepared.
[0022] As a control, 1.0 g of noble metal precursors Pd(acac)2, Pt(acac)2, Ru(acac)3 or Ir(acac)3 or active component metal salt Cu(acac)2 were weighed and added to 50 mL of oleylamine. Then, 0.56 g of vitamin C and 0.72 g of CTAB were added, and the mixture was heated to 180 °C for 5 h. After the reaction was completed, the reaction solution was centrifuged (8000 rpm, 5 min, leaving the precipitate), washed (the washing agent was a mixture of cyclohexane and ethanol in a volume ratio of 5:1), and dried (60 °C) to obtain the catalysts, which were denoted as G, H, I, J, and K, respectively.
[0023] The specific metal components of each catalyst are shown in Table 2.
[0024] Table 2. Metal composition of each catalyst
[0025] Each of the above catalysts was modified onto carbon paper to prepare electrode sheets. The specific modification methods are as follows: (1) Take 1 mL of ethanol, add 20 μL of Nafion solution (as a binder) and 1 mg of catalyst powder, mix well, and sonicate for 2 h to obtain a catalyst slurry; (2) The catalytic slurry is drop-coated onto carbon paper and dried. In this specific embodiment, the carbon paper used is 1cm × 1cm in size, and the electrode sheet has an area of 1cm². 2 .
[0026] II. Preparation of Electrolyte Water and ethanol were mixed at a volume ratio of 3:1, and then the electrolyte 1-ethyl-3-methylimidazolium tetrafluoroborate ([EMIm]BF4) was added to make the concentration of [EMIm]BF4 0.2 mg / mL, thus obtaining the electrolyte solution.
[0027] In this electrolyte: (1) Water: provides a source of protons.
[0028] (2) Ethanol: provides a reaction medium, enhances the solubility of organic substrates, and activates the carbonyl group of organic substrates through hydrogen bonding; (3) [EMIm]BF4: broadens the available potential window, supports high-voltage electrochemical systems; improves system safety and stability; regulates ion transport characteristics and optimizes reaction kinetics; suppresses solvent co-intercalation / side reactions and protects electrode structure.
[0029] III. Electrochemical Synthesis of Syringaldehyde Compounds
[0030] Example 1
[0031] Add the prepared electrolyte (0.7 mL) to a diaphragmless electrolytic cell. The electrolytic cell dimensions are: 1 cm long × 1 cm wide × 1 cm high. Use electrode plates modified with catalysts Pd-1, Pd-2, Pd-3, Pd-4, Pd-5, Pd-6, or Pd-7 as the anode and cathode of the electrolytic cell, with a 1 cm distance between the anode and cathode.
[0032] Add 0.3 mL of the reaction substrate 3-(4-hydroxy-3,5-dimethoxyphenyl)acrylic acid to the electrolyte, add a magnetic stir bar, and set the electrolytic cell potential to -0.9 V and the current to 100 mA (current density 100 mA·cm⁻¹). -2 The temperature is 30℃, and the substrate is reduced using a constant current method. The electrolysis principle is as follows: .
[0033] During the reaction, the reaction progress was monitored using thin-layer chromatography (TLC). Monitoring showed that the reaction was complete after 10 hours of electrolysis. The reaction solution was rotary evaporated (to remove ethanol) to obtain a mother liquor, which was then washed with petroleum ether (to remove the byproduct acetic acid). The mother liquor washed with petroleum ether was then purified with ethyl acetate and finally dried (at 60°C) to obtain a white powdery product.
[0034] The white powdery product 1 H-NMR, 13 The C-NMR and MS detection results are shown in the table below. Figure 4 , Figure 5 and Figure 6 .
[0035] Depend on Figure 4 , Figure 5 and Figure 6 It can be seen that the peak shift of the white powder product prepared in this embodiment conforms to the structure of syringaldehyde. This proves that the electrochemical method provided by this invention can successfully prepare syringaldehyde-like compounds.
[0036] The selectivity, yield, and Faraday efficiency of the target product vary slightly depending on the electrode used, as detailed in Tables 3-1 to 3-5.
[0037] Table 3-1 Effect of Catalyst Type on Target Product (Part 1)
[0038] Table 3-2 Effect of Catalyst Type on Target Product (Part 2)
[0039] Table 3-3 Effect of Catalyst Type on Target Product (Part 3)
[0040] Table 3-4 Effect of Catalyst Type on Target Product (Part 4)
[0041] Table 3-5 Effect of Catalyst Type on Target Product (Part 5)
[0042] As shown in Tables 3-1 to 3-5, bimetallic catalysts formed by noble metals (Pd, Pt, Ru, or Ir) and transition metal elements (Pb, In, Sn, Fe, Ga, Al, or Cu) all exhibit good catalytic performance; while catalysts formed by single metals (Pd, Pt, Ru, Ir, or Cu) have poor catalytic performance.
[0043] Analysis of the reasons: Platinum group metals (Pt, Ru, Ir, Pd, etc.) provide high conductivity and the fundamental ability to adsorb and activate substrate molecules. The introduction of oxyphilic metals such as Al, Ga, In, Sn, Pb, Fe, Cu can modulate the electronic structure of Pt group metals. By forming heterojunctions, the d-band center of Pt group metals can shift downward, weakening the adsorption of H, thereby strongly inhibiting the electrocatalytic hydrogen evolution reaction (HER), while enhancing the specific adsorption and activation of key functional groups such as C=O or C=C in the substrate. Single-metal catalysts such as Pt, Ru, Ir, Pd, and Cu, due to the weak adsorption between these metal atoms and substrate molecules, cannot activate the substrate and ultimately cannot undergo efficient reactions.
[0044] Example 2 Based on Example 1, the electrolysis conditions (potential, temperature, electrolyte) were changed to investigate the effect of the electrolysis conditions on the target product.
[0045] Group 1: Electrode sheets modified with catalyst Pd-1 are used as the anode and cathode of the electrolytic cell, which is not powered on.
[0046] Group 2: Electrode sheets modified with catalyst Pd-1 were used as the anode and cathode of the electrolytic cell, and the potential of the electrolytic cell was set to 3.5V.
[0047] Group 3: Electrode sheets modified with catalyst Pd-1 were used as the anode and cathode of the electrolytic cell, and the temperature was set at 80℃.
[0048] Group 4: Electrode sheets modified with catalyst Pd-1 were used as the anode and cathode of the electrolyzer, and water in the electrolyte was replaced with acetonitrile and ethanol was replaced with methanol.
[0049] Chromatographic characterization revealed that the target product was not detected in any of the four groups.
[0050] Example 3 Based on Example 1, the reaction substrate was changed, and the selectivity of the catalyst for the reaction substrate was investigated.
[0051] Group 1: Electrode sheets modified with catalyst Pd-1 were used as the anode and cathode of the electrolytic cell. The reaction substrate was replaced with 3-(4-hydroxy-3,5-dimethoxyphenyl)acrylic acid at a volume of 0.3 mL.
[0052] Group 2: Electrode sheets modified with catalyst Pd-1 were used as the anode and cathode of the electrolytic cell. The reaction substrate was replaced with 3-(4-hydroxy-3,5-dimethoxyphenyl)acrylic acid at a volume of 0.3 mL.
[0053] The HPLC detection results of the first group of products are shown in the figure. Figure 7 , 1 The H-NMR detection results are shown in […]. Figure 8 , 13 The C-NMR detection results are shown in […]. Figure 9 The HPLC results of the second group of products are shown in [the table below]. Figure 10 , 1 The H-NMR detection results are shown in […]. Figure 11 , 13 The C-NMR detection results are shown in […]. Figure 12 .
[0054] Depend on Figures 7 to 12 It can be seen that both groups yielded syringaldehyde compounds.
[0055] The test results showed that the selectivity, yield, and Faraday efficiency of the first group of products were 97%, 93%, and 98%, respectively, while the selectivity, yield, and Faraday efficiency of the second group of products were 95%, 92%, and 97%, respectively.
[0056] IV. Investigating the long-term cycling stability of the electrodes Cathode and anode: Electrode sheets modified with catalyst Pd-1 prepared in Example 1.
[0057] Electrolyte: Ethanol-water-[EMIm]BF4 system (mix water and ethanol at a volume ratio of 3:1, then add [EMIm]BF4 to achieve a [EMIm]BF4 concentration of 0.2 mg / mL).
[0058] Reaction substrate: 3-(4-hydroxy-3-methoxyphenyl)acrylic acid.
[0059] Evaluation indicators: substrate conversion rate, syringaldehyde selectivity, and Faraday efficiency.
[0060] Long-term cyclic stability testing of the electrodes was conducted using a continuous flow electrolytic cell. Specifically: The Pd-1 modified electrode sheets prepared in Example 1 were assembled into the cathode and anode of a two-electrode flow electrolyzer, respectively. The reaction substrate was continuously fed into the reaction chamber at a flow rate of 2 mL·min⁻¹ using a peristaltic pump. The constant current was controlled at 100 mA, and the electrolyte temperature was maintained at 25±1°C. Samples were taken every 50 h, and the substrate content was detected by high performance liquid chromatography (HPLC). The substrate conversion rate, syringaldehyde selectivity, and Faraday efficiency were calculated.
[0061] Table 4 shows the calculated results of substrate conversion, syringaldehyde selectivity, and Faraday efficiency. The variation of Faraday efficiency is shown in [the table below]. Figure 13 .
[0062] Table 4. Calculation results of substrate conversion, syringaldehyde selectivity, and Faraday efficiency.
[0063] From Table 4 and Figure 13 It can be seen that the electrode plate modified with catalyst Pd-1 prepared in Example 1 still maintains more than 90% of its initial activity, substrate conversion rate of 99%, and syringaldehyde selectivity of 97% after 350 hours of continuous operation, indicating that the electrode has excellent long-term cycling stability.
[0064] It should be noted that the above embodiments are merely examples for clearly illustrating the present invention, and are not intended to limit the implementation of the present invention. Those skilled in the art can make other variations or modifications based on the above description. It is impossible to exhaustively list all possible implementations here. All obvious variations or modifications derived from the technical solutions of this invention are still within the scope of protection of this invention.
Claims
1. A method for the electrochemical synthesis of syringaldehyde compounds using phenyl-containing acrylic acid derivatives as substrates, characterized in that, Includes the following steps: (1) The active metal components Pb, In, Sn, Fe, Ga, Al or Cu are decorated on the surface or interface of platinum group metals Pd, Pt, Ru or Ir in the form of oxides or atomic dispersions to accurately construct a heterojunction structure and obtain a catalyst. The specific method for constructing the heterojunction structure is as follows: (i) Take 1.0 g of platinum group metal precursor and add it to oleylamine, then add 0.56 g of vitamin C and 0.72 g of CTAB, and react at 180 °C for 5 h to obtain precursor nanoparticles; (ii) The precursor nanoparticles were separated, purified, and dried, and then added to ethanol containing 4g of nano-sized conductive carbon black and ultrasonically mixed. They were then separated and dried again to obtain product A. (iii) Add all of the product A by mass to the active component metal salt, stir evenly, let stand at room temperature for 0.5 h, then dry at 60 °C, and finally calcine at 200 °C for 2 h. (2) The catalyst is modified onto carbon paper to form an electrode sheet; (3) Prepare a water-ethanol-[EMIm]BF4 electrolyte system; (4) Add the electrolyte to the diaphragmless electrolytic cell, use the electrode plates as the anode and cathode of the electrolytic cell, add a phenyl-containing acrylic acid derivative to the electrolyte, wherein the phenyl-containing acrylic acid derivative is 3-(4-hydroxy-3,5-dimethoxyphenyl)acrylic acid, 3-(4-hydroxy-3-methoxyphenyl)acrylic acid, or 3-(4-hydroxyphenyl)acrylic acid, set the potential of the electrolytic cell to -0.9V, and the current density to 100mA·cm. -2 The reaction substrate was reduced at 30℃ using a constant current method. After the reaction was complete, the product was separated, purified, and dried.
2. The method for electrochemically synthesizing syringaldehyde compounds using phenyl-containing acrylic acid derivatives as substrates according to claim 1, characterized in that, In step (i), the platinum group noble metal precursor is Pd(acac)2, Pt(acac)2, Ru(acac)3 or Ir(acac)3.
3. The method for electrochemically synthesizing syringaldehyde compounds using phenyl-containing acrylic acid derivatives as substrates according to claim 1, characterized in that, In step (iii), the active component metal salt is Pb(acac)2, InCl3, SnCl2, Fe(acac)3, Ga(acac)3, AlCl3 or Cu(acac)2.
4. The method for electrochemically synthesizing syringaldehyde compounds using phenyl-containing acrylic acid derivatives as substrates according to claim 1, characterized in that, In step (2), the method for modifying the catalyst onto the carbon paper is as follows: (i) Mix ethanol, Nafion solution and catalyst powder evenly, and sonicate to obtain a catalyst slurry; (ii) Apply the catalytic slurry onto carbon paper and let it dry.
5. The method for electrochemically synthesizing syringaldehyde compounds using phenyl-containing acrylic acid derivatives as substrates according to claim 1, characterized in that, In step (3), the method for preparing the water-ethanol-[EMIm]BF4 electrolyte system is as follows: Water and ethanol were mixed at a volume ratio of 3:1, and then [EMIm]BF4 was added to make the concentration of [EMIm]BF4 0.2 mg / mL.
6. The method for electrochemically synthesizing syringaldehyde compounds using phenyl-containing acrylic acid derivatives as substrates according to claim 1, characterized in that, In step (4), the methods for separating, purifying, and drying the product are as follows: (i) Rotary evaporation of the reaction solution yields the mother liquor; (ii) Wash the mother liquor with petroleum ether; (iii) Purify the mother liquor after washing with petroleum ether using ethyl acetate; (iv) The purified mother liquor was dried at 60°C.
Citation Information
Patent Citations
Method for electrochemical synthesis of syringaldehyde by using water as oxygen source
CN113073347A
Electrochemical method for pairwise synthesizing syringic acid and adiponitrile
CN121674980A